The Politics of Thai Silk during the Colonial Period to the Cold War Era - Pongyelar, Suppakarn (Kasetsart Journal of Social Sciences, 2015)
The Thai government's policy on silk promotion dates back to the reign of King Rama V with the political objective to balance colonial powers. After its failure, the promotion was thus short-lived. However, Thai silk promotion was again advocated by an ex-American CIA agent turned silk entrepreneur, Jim Thomson, and then by the Royal House in the Cold War period in order to cope with communist insurgency in the northeastern part of the country—the home of Thai silk production. Since then Thai silk, as a traditional livelihood, has been symbolized as a ‘Thai identity’ with success. Yet, the development of the Thai silk cottage industry is still limited as it has not been promoted and developed seriously. This article scrutinized the politics of the Thai silk development policy and the construction of Thai silk as a "Thai identity" and pointed out that it was political contexts that shaped the image and significance of the Thai silk industry while its silk cottage industry was left behind.